Comparative clinical study of the effectiveness of translingual neurostimulation in patients with post-stroke cognitive impairment. - Farkhad , Alkhanov; Gaukhar , Abassova; Gulnaz , Kaishibayeva; Balzhan, Baizhan BalzhanBaizhan; Alma , Aitbembetova; Saltanat, Serikbayeva (Bangladesh Journal of Medical Science, 2025)
Background The most important cerebrovascular pathology leading to cognitive impairment is ischemic strokes. Cognitive impairment is one of the most common clinical manifestations of cerebral stroke, which, along with motor disorders, leads to significant restrictions in the household and social spheres, reduces adherence to treatment, and limits the effectiveness of ongoing rehabilitation measures. Objectives The aim of the study was to evaluate the effectiveness of translingual neurostimulation in the rehabilitation of post-stroke cognitive disorders in comparison with individual corrective procedures with a psychologist. Materials and methods The study involved 180 patients who had suffered an ischemic stroke between 2023 and 2024. Men-118 (65.5%), women-62 (34.5%). The data was collected by conducting tests on the MMSE, Bartel, NIHSS, Merton and Sutton scales. The main group included 60 patients who, in addition to comprehensive rehabilitation treatment, underwent translingual neurostimulation with a Neuroport device. The active control group consisted of 60 patients who, in addition to standard rehabilitation, underwent a course of individual corrective procedures with a psychologist as cognitive training. In the passive control group, represented by 60 patients, only standard rehabilitation was performed. Results According to the MMSE scale results:The first main group shows the best performance (Me ≈ 4.00), surpassing the second and third groups. According to the presented results of the Barthel scale: The first group showed the best result (Me ≈ 20.00), which is significantly higher than in the second and especially in the third group. The NIHSS scale was directed downwards (lower values are better). Where the first group has the lowest Me ≈ -4, which is better than the second group Me ≈ -3 and the third group Me ≈ -2. According to the analysis of the Merton and Sutton scale data, the first group has a significant superiority of Me ≈10, in contrast to the second group, Me ≈ 7 and the third group, Me ≈ 5. Statistically significant differences between the groups were confirmed (p < 0.001). Conclusion Translingual neurostimulation has confirmed its effectiveness in the recovery of post-stroke cognitive impairments in comparison with the course of standard rehabilitation, as well as individual corrective procedures with a psychologist. BJMS, Vol. 24 No. 03 July’25 Page : 946-949